GAMBARAN GAYA HIDUP PASIEN HIPERTENSI DI PUSKESMAS KOYA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA - Songut, Adriana Lea; Mautang, Theo W. E.; Pongoh, Lucyana L. (Yayasan Syalom Cipta Sumikolah, 2024)
The aim of this research is to determine the lifestyle of hypertensive patients at the Koya Community Health Center, South Tondano District, Minahasa Regency, North Sulawesi Province. To determine smoking habits, physical activity, eating and drinking habits, stress or anxiety levels of hypertensive patients at the Koya health center. The type of research used in this research is descriptive research. This type of research was used to determine the lifestyle of hypertensive patients at the Koya Community Health Center, South Tondano District, Minahasa Regency, North Sulawesi Province. The research results showed that respondents had active smoking habits at a moderate level (50.0%), while only a small portion were in the high category (13.5%). Then the level of exposure to passive smoking is low (61.5%). However, there was also a significant proportion of patients who experienced moderate (17.3%) and high (21.2%) exposure. Furthermore, respondents had less physical activity (55.8%), while the remainder (44.2%) had a sufficient level of physical activity. Respondents have good eating and drinking habits (76.9%), while the remainder (23.1%) still have habits that need improvement and the majority are in the categories of symptoms of stress (38.5%) and mild stress (36.5%). However, there were also significant proportions who experienced moderate stress (11.5%) and severe stress (13.5%).